MEDIA PEMBELAJARAN INOVATIF SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH: SUATU KAJIAN PUSTAKA - Desak Nyoman Alit Sudiarthi (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
The current phenomenon indicates the quality of learning or the quality of education in general is a challenge during the corona pandemic or covid-19. It can be seen that teaching and learning activities between educators and students which were originally conducted through direct interaction in the classroom are not able to be carried out. Face-to-face or direct interaction in class should be limited or even eliminated in order to prevent the spread of the virus. It means that the health protocol requires each individual to practice social and physical distancing in conducting teaching and learning interactions. Due to the pandemic, teaching and learning activities suddenly have to be implemented by a distance learning system via the internet/online learning network. In fact, not all educators and students meet the eligibility requirements for conducting online learning activities. To address it, we invite all education stakeholders to participate in finding solutions and anticipating these problems. The solution is the concept of innovative learning media requiring to be developed in designing learning, understanding the distance learning system, and maximizing the use of innovative learning media in carrying out teaching and learning activities. Key words: Innovative Learning Media, Distance Learning